2022
DOI: 10.3389/fphys.2022.904778
|View full text |Cite
|
Sign up to set email alerts
|

Lockdown Duration and Training Intensity Affect Sleep Behavior in an International Sample of 1,454 Elite Athletes

Abstract: Objective: To investigate the effect of 1) lockdown duration and 2) training intensity on sleep quality and insomnia symptoms in elite athletes.Methods: 1,454 elite athletes (24.1 ± 6.7 years; 42% female; 41% individual sports) from 40 countries answered a retrospective, cross-sectional, web-based questionnaire relating to their behavioral habits pre- and during- COVID-19 lockdown, including: 1) Pittsburgh sleep quality index (PSQI); 2) Insomnia severity index (ISI); bespoke questions about 3) napping; and 4) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 31 publications
2
32
0
Order By: Relevance
“…Collaterally, decreases in training were linked with higher depression, anxiety, and stress symptoms during the COVID-19 lockdown ( Facer-Childs, et al, 2021 ). Some elite athletes reported psychological distress due to training cessation during lockdown ( di Cagno et al, 2020 ; Jia et al, 2022 ; Venturelli et al, 2022 ), changes in sleep ( Facer-Childs et al, 2021 ; Romdhani et al, 2022b ), financial problems, among others. In the current study, the majority of athletes reported financial difficulties, especially among individual-sport, and World-Class athletes; an extra stressor that potentially impacted the athletes’ mental health ( Busch et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Collaterally, decreases in training were linked with higher depression, anxiety, and stress symptoms during the COVID-19 lockdown ( Facer-Childs, et al, 2021 ). Some elite athletes reported psychological distress due to training cessation during lockdown ( di Cagno et al, 2020 ; Jia et al, 2022 ; Venturelli et al, 2022 ), changes in sleep ( Facer-Childs et al, 2021 ; Romdhani et al, 2022b ), financial problems, among others. In the current study, the majority of athletes reported financial difficulties, especially among individual-sport, and World-Class athletes; an extra stressor that potentially impacted the athletes’ mental health ( Busch et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sleep quantity and quality are of paramount importance for recovery and performance of the athletes. Reduced training intensity and fewer training sessions result in circadian interference, which negatively impacts sleep quality ( Romdhani et al, 2022b ) and could potentially trigger mental health issues ( Facer-Childs et al, 2021 ), such as elevated stress and depression ( Facer-Childs et al, 2021 ; Romdhani et al, 2022b ). In this context, high intensity training can promote 1) increased sleep drive contributing to improved sleep ( Romdhani et al, 2022b ) and 2) activation of endogenous opioid release (inside the brain) resulting in mood elevation and stress reduction ( Saanijoki et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing evidence from the international literature suggests that people from a range of populations became less active and/or increased sedentary activities during the pandemic [12][13][14][15][16][17][18]. Considering older adults, evidence from a German and an international study both suggest that containment measures from the early stages of the pandemic (April-June 2020) had a deleterious effect on energy expenditure and frequency of physical activity [14,18].…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 enters the body through the eyes, nose, or mouth and is transmitted through droplets emitted when sneezing, coughing, or speaking [13][14][15][16][17]. Several social distancing and prevention and treatment measures have been implemented by governments around the world to protect the population and the health services that treat them, with the goal of eliminating this once immunity is achieved through vaccination and improvements in treatment are made [18][19][20][21][22][23][24][25][26][27][28].…”
mentioning
confidence: 99%